2012
DOI: 10.1200/jco.2011.40.0887
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Circulating Tumor Cells and Prognosis in Patients With Stage III Melanoma With Sentinel Lymph Node Metastasis in a Phase III International Multicenter Trial

Abstract: CTC biomarker status is a prognostic factor for recurrence-free survival, distant metastasis disease-free survival, and MSS after CLND in patients with SLN metastasis. This multimarker RT-qPCR analysis may therefore be useful in discriminating patients who may benefit from aggressive adjuvant therapy or stratifying patients for adjuvant clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 44 publications
0
68
1
2
Order By: Relevance
“…Hence, epithelial expression-based methods such as the CellSearch device, may have a disadvantage (despite being the only FDA approved CTC isolation device) over expressionindependant, filtration-type platforms such as ISET (RareCells, Paris, France) or ScreenCell which rely on cell size and other physical cellular properties. There are a multitude devices available on the market, with varying functionality (19)(20)(21)(22)(23)(24)(25) The CTC detection rate by ScreenCell in our study, was higher compared to similar studies looking at patients with early-stage NSCLC. Freidin et al (2014) reported CTC detection rates of 56% and 65% by two separate pathologists using ScreenCell in patients undergoing surgery for early-stage lung cancer in comparison to 78.3% (N=15) and 73.9% (N=14) detection rates in our study (Table II) (26).…”
Section: Discussioncontrasting
confidence: 47%
“…Hence, epithelial expression-based methods such as the CellSearch device, may have a disadvantage (despite being the only FDA approved CTC isolation device) over expressionindependant, filtration-type platforms such as ISET (RareCells, Paris, France) or ScreenCell which rely on cell size and other physical cellular properties. There are a multitude devices available on the market, with varying functionality (19)(20)(21)(22)(23)(24)(25) The CTC detection rate by ScreenCell in our study, was higher compared to similar studies looking at patients with early-stage NSCLC. Freidin et al (2014) reported CTC detection rates of 56% and 65% by two separate pathologists using ScreenCell in patients undergoing surgery for early-stage lung cancer in comparison to 78.3% (N=15) and 73.9% (N=14) detection rates in our study (Table II) (26).…”
Section: Discussioncontrasting
confidence: 47%
“…Furthermore, tumor tissue may not always be available for analysis, particularly when metastases are small or when biopsy or surgery is not technically feasible. CTC can provide a real-time evaluation of subclinical melanoma spread and a method for monitoring patient response to therapy (1,6,29 ). The study of genomic aberrations in CTC may provide insight into genomic characteristics and mechanisms by which tumor cells establish distant organ metastasis and lead to the development of strategies to target CTC to prevent or control systemic melanoma metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Since this technique was first described by Smith et al in 1991, using tyrosinase mRNA PCR analysis, several additional candidate mRNA biomarkers have been proposed, including [56,57]. However, research groups tend to agree on the basic principles of the technique.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…The primary strength of mRNA analysis is its ease of acquisition and scalability (Table 1). reverse transcriptase PCR studies have already been successfully embedded in international multicenter clinical trials involving more than 1,000 patients in total [54,56,57]. However, mRNA analysis has not yet been used to identify key genetic abnormalities in melanoma, such as BRAF, c-Kit, and PTEN (phosphatase and tensin homolog).…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation